Special Education in the state of Rio Grande do Sul: History, politics and management (1970-1980) - Severo, Andréa Asti; da Silva, Mayara Costa; Baptista, Claudio Roberto (Education Policy Analysis Archives, 2019)
This text presents an analysis related to special education, in Rio Grande do Sul, between 1970 and 1980. The research was based on the analysis of bibliographical and historical documents on the subject, such as a report of a Special Commission of the State Legislative Assembly from 1972. The period analyzed is marked by educational reforms and by the predominance of a military regime that, in addition to its authoritarian dimension, privileged the perspective of privatization of services. It is possible to identify the predominance of an understanding of special education as a “problem” to be corrected and which was associated with an educational policy perspective based on the ideal of homogenization through initiatives that favored the assistance and the private sector.